Embedded System Technology Spillover Effects of Digital Economy and High-Quality Economic Development - Gao, Jian (EAI Endorsed Transactions on Scalable Information Systems, 2024)
INTRODUCTION: With the development of digital technology and computer technology, the theory of digital economy has also had far-reaching development, but at present, the digital economy is still not able to clearly define whether the digital economy is good or bad for the high-quality development of China’s economy. Therefore, it is necessary to research the spillover effect of the digital economy and the high-quality development of the economy with the help of embedded system technology. OBJECTIVES: To solve the issue of the poor coupling between the digital economy and high-quality development, to raise the degree of China’s digital economic development, to improve the high energy consumption in the course of China’s economic high-quality development, and to improve the application level of system technology in the study of China’s economic development. METHODS: The digital economy model is established using the entropy weight method; its efficiency is evaluated using embedded system technology; the spillover effect analysis of high-quality development is then conducted using the digital economy index; and lastly, the overall assessment of the spillover effect is conducted using the comprehensive evaluation results of the entropy weight method. RESULTS: Embedded system technology has a noticeable promotion effect on the development of the digital economy; although the development of the digital economy and economic high-quality development are poorly coupled, their promotion effect is more significant; embedded system technology can indirectly promote the development of economic high-quality development through the digital economy. CONCLUSION: China should vigorously develop embedded system technology to promote the application of new technology in the economy and should further standardize the market economic order to maintain the orderly development of the digital economy.